Scanning Models of Food Systems Resilience in the Indo-Pacific Region - Friedman, Rachel S.; England, Rachel M.; Ricketts, Katie D.; van Wensveen, Monica; Lim-Camacho, Lilly; Crimp, Steven (Frontiers in Sustainable Food Systems, 2022)
The Indo-Pacific is a region of the world experiencing rapid growth in population and development. However, it is also exposed to a number of social, economic, geopolitical, and biophysical stressors, which may undermine the region’s ability to support its population, ensure food security, and sustain livelihoods. In response to the complex suite of stressors, a number of development initiatives and research programs have been established to build resilience in the region’s food systems. These initiatives vary in scope and scale, but also in what they mean by the term resilience and the components of the food system they address. This variation has implications for the outcomes of these efforts and how well they match a theoretical ideal of resilience. This review examines how resilience and food systems are defined, conceptualized, and applied within research studies and projects or initiatives on food systems resilience funded or supported by national, regional, or multilateral government, and non-governmental institutions in the Indo-Pacific region. It also compares how the concepts are treated from an academic or theoretical perspective versus in practical applications. We take a two-pronged approach: first, identifying organizations engaged in the Indo-Pacific region and developing an inventory of initiatives and projects that have bearing on food systems resilience; and second, carrying out literature searches to record research studies in the region that examine resilience within food systems. We then identify any formalized frameworks or definitions of resilience and/or food systems guiding these projects and studies. The results indicate there is a heavy focus on climate change and natural disasters, and to a lesser extent health-related shocks, in food systems resilience research and practice. Definitions, however, are inconsistently reported, and often more simplistic than resilience theory depicts, favouring resilience conceptualizations around adaptation and a production-oriented food systems framing. While the specific definitions vary between research and applied projects, the fragmented and ambiguous use of terms presents a challenge for policy applications and coordination. Overall, establishing some clear guiding resilience principles, modified according to contextual factors, could enable more streamlined resilience work in Indo-Pacific food systems.